Turkish folk medicinal plants, part VII: Ezine (Çanakkale) - (:unkn) unknown (My University, 2007)
In this study, 66 folk medicinal plants from Ezine (Çanakkale) are presented. Among them 49 species are wild and 17 species are cultivated plants. The folk medicinal plants are mostly used for stomach ailments, diabetes, hemorrhoids, kidney stones, cold, wound and eczema.
Keywords: Çanakkale; Ezine; Folk medicine; Medicinal plants; Turkey